Potensi Ekstrak Bunga Telang (Clitoria ternatea L.) sebagai Larvasida Alternatif Larva Aedes albopictus Instar III - Lukiyono, Yauwan Tobing; Hidayat, Muhammad Taufiq; Sunaryo, Merry; Nidianti, Ersalina; Zain, Salfa Salsabilah; Sari, Yuni Nur Malita; Putri, Ngiluhtara Aditiya (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the Dengue Virus, which is carried by vectors. One of which is the Aedes albopictus. DHF case data in Indonesia in 2016 was reported to reach 204,171 cases (IR 78.85/100,000 population) with a mortality rate of 1,598 people (CFR 0,78%). The most common way to control DHF is chemically using synthetic insecticides. Improper use of chemicals can have negative impacts, such as the death of non-target organisms, environmental pollution and vector resistance. Because of this impact, efforts are needed to use natural larvicides derived from natural ingredients to kill mosquito larvae that are safe for the environment, one of which is larvicides from butterfly pea flower extract. Based on this description, this study aims to determine the potential of butterfly pea flower extract (C. ternatea L.) on the death of A. albopictus larvae. This research is a pure experimental research. The control group in this study consisted of positive controls using 1% Abate and negative controls using distilled water. The experimental group was the administration of butterfly pea flower extract (C. ternatea L.) to A. albopictus larvae with varying concentrations of 30% and 40%. From the results of research on the potential of butterfly pea extract as an alternative larvicidal of A. albopictus larvae, it can be concluded that the butterfly pea extract has a larvicidal effect on A. albopictus larvae. The concentration of butterfly pea extract has the potential to kill A. albopictus larvae with an LC50 value obtained at a concentration of 39.815%.